The Ability of The Fourth Semester Students in Constructing Passive Voice in Writing Explanatory Essay: A study at the English Department FBS UNP Padang - Rima Yunita; Hermawati Syarif; Fitrawati Fitrawati (English Language Teaching and Research, 2017)
This study is aimed to describe the ability of the fourth semester English department students at UNP, who are registered in 2015/2016 academic year, in constructing passive voice in writing explanatory essay. This study is also aimed to find out grammatical problems in constructing passive voice. This is a descriptive quantitative research. Proportional random sampling technique was used to determine the sample. The data were collected by using writing test with four alternative topics, one of which should be chosen. Students were asked to write passive sentences in their essay. Based on the findings of the research, it was found that students’ ability in constructing passive voice is in average level. There are four common grammatical problems identified from the students’ writing, which are grammatical problems related to the use of auxiliary be (22%), the use of past participle verb (46%), the agreement of subject and auxiliary (20%), and the choice of voice that should be used to construct the sentences (12%). V1, Ving, and incorrect form of past participle verb were used to replace the use of past participle verb in students’ passive sentences. In addition, incorrect forms of auxiliary and missing auxiliary were found to be the students’ problem. It was also found that students constructed active voice for sentences that should be written in passive voice since it is the subject that must receive the action. Key words/phrases: passive voice, explanatory essay, ability